An investigation into the feasibility of implementing activity-based costing in a local, family-owned manufacturing firm : a case study. - Cheong, Chi Kit. (2009)
The goal of any cost management system is to provide relevant and timely information to the management. The object of this case study is to apply the concepts of activity-based costing, as initiated by Kaplan, to a local manufacturing firm involved in the production of polystyrene products. The subject firm has been chosen due to the circumstances under which the firm is operating: high volume sales at low unit prices of many end products provide a suitable situation to explore the application of activity-based costing to assist management in arriving at a more accurate costing of products and, ultimately, in making better management decisions.